Library of Congress Subject Headings Related to Indigenous Peoples: Changing LCSH for Use in a Canadian Archival Context. Issue 1 (2nd January 2018) - Bone, Christine; Lougheed, Brett
ABSTRACT: The Association for Manitoba Archives has created a database where members can deposit archival descriptions to provide a central search for users. Library of Congress Subject Headings (LCSH) were chosen as the controlled subject vocabulary to use in the descriptions, but changes were made to LCSH to better describe material about or by Indigenous peoples. Examples include: the word "Indian"; geographic place embedded in terms such as "Indians of North America"; changes related to Manitoba peoples specifically; and miscellaneous changes not part of a larger pattern. New terms were also added.